Correlates of occupational aspirations of male teachers - Samson, Pedro V. 1932- (s.n.], 1971)
This study sought to identify the correlates of occupational aspirations of male teachers and to provide baseline data for policy making in the recruitment, grade assignment and promotions of male teachers, for the study of the occupational aspirations of male teachers in the whole country, and for the study of the causes of turnover of male teachers. It is hereby concluded that the correlates of occupational aspirations are educational attainment, teaching experience, civil